1986
DOI: 10.1182/blood.v67.4.1176.bloodjournal6741176
|View full text |Cite
|
Sign up to set email alerts
|

Cultured human endothelial cells synthesize a plasma membrane protein complex immunologically related to the platelet glycoprotein IIb/IIIa complex

Abstract: We have previously demonstrated that endothelial cells synthesize a plasma membrane protein indistinguishable from platelet glycoprotein (GP) IIa. The present study provides evidence for a further analogy between the platelet and the endothelial cell membrane by showing that cultured endothelial cells also synthesize a membrane protein complex immunologically related to the platelet GP IIb/GP IIIa complex. This evidence is based on the following observations: (1) C17, a murine monoclonal antiplatelet GP IIIa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…8). The GPIIb/Ma complex was immunoprecipitated from t25I-surface labeled HUVE with the anti-GPIIb/IIIa antibody (data not shown), similar to results described by others (Fitzgerald et al, 1985;Leeksma et al, 1986;Newman et al, 1986). Additionally, with platelet sample the polyclonal antibody cross-reacts with GPIIb (Fig.…”
Section: Specificity Of Anti-gpilb/llia Iggsupporting
confidence: 85%
See 2 more Smart Citations
“…8). The GPIIb/Ma complex was immunoprecipitated from t25I-surface labeled HUVE with the anti-GPIIb/IIIa antibody (data not shown), similar to results described by others (Fitzgerald et al, 1985;Leeksma et al, 1986;Newman et al, 1986). Additionally, with platelet sample the polyclonal antibody cross-reacts with GPIIb (Fig.…”
Section: Specificity Of Anti-gpilb/llia Iggsupporting
confidence: 85%
“…Unlike its counterpart on platelets, the formation of the GPIIb/IIIa complex on endothelial cells does not seem to be Ca2+-dependent (Fitzgerald et al, 1985). The molecular weights of GPIlb/IIIa-like proteins in endothelial cells are also slightly different from platelets (Thiagarajan et al, 1985;Fitzgerald et al, 1985;Leeksma et al, 1986). In that platelet GPIIb/IIIa binds to molecules contained in the extracellular matrix, it is possible that HUVE detachment by anti-GPIlb/IIIa IgG is due to disruption of interactions of GPIlb/IIIa complex with fibronectin, vitronectin, thrombospondin, or some other protein(s) located in the subendothelial matrix .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it does not recognize other GPIIa-containing complexes, the epitope probably resides on GPIa. Monoclonal antibody CLB-C17, directed against GPIIIa, has been described before (Tetteroo et al, 1983;Leeksma et al, 1986). Monoclonal antibodies Sam-1, GoH3 and K20 are directed against epitopes on different VLA subunits: Sam-1 against an epitope on VLAa5 (unpublished), GoH3 against an epitope on VLAa6 (Sonnenberg et al, 1987;Hemler at al, 1988) and K20 against an epitope on VLAB (Leucocyta Typing IV, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…HUVE synthesizes GPIIIb, GPII,, and GPIIbIII,-like substances, and antibodies for human platelet might bind to HUVE [3,4,9,10]. Therefore, we studied the binding of anti-platelet GPII&I, (a major component of platelet membrane) monoclonal antibodies to HUVE after its exposure to TTP sera and found that treatment with TTP sera significantly lowered the binding rate.…”
Section: Discussionmentioning
confidence: 99%